The Effect of the Teaching Games for Understanding Learning Model on the Learning Motivation of Grade VIII Students in Athletics at SMPN 1 Ambalawi - Muhamad Januar Ansyari; Ainun Fitriani; Anhar Anhar; Anas Ardiansyah; Mardian Andriani (Jurnal Ilmiah Mandala Education (JIME), 2025)
Introduction: In implementing physical education and health learning, a pleasant learning atmosphere is needed with the aim of increasing students' interest and motivation in learning.Materials and Methods: This study used a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 20 eighth-grade students selected based on initial observations, 60% of whom showed low learning motivation. Data collection was conducted by administering learning motivation questionnaires before (pretest) and after (posttest) the application of the TGFU model. The pretest and posttest data were then analyzed using a paired sample t-test to determine the significance of the difference in learning motivation before and after the intervention.Results: The results showed a significant increase in student learning motivation. The average pretest score of 68.45 (with a mastery level of 46%) increased to 126 (mastery level of 84%) on the posttest. This increase shows that TGFU can create a more enjoyable, interactive learning atmosphere that is in line with the developmental needs of students.Conclusion: The TGFU learning model is effective in increasing students' learning motivation in athletics. This approach can be presented as an innovative learning alternative in physical education because it encourages active student involvement and provides meaningful learning experiences.